Development and Validation of a Principal Performance Assessment Instrument to Support Technology-Enhanced Biology Learning and Environmental Literacy in Secondary Schools - Ivatul Laily Kurniawati; Dhamas Mega Amarlita; Mursaid Dahlan (INSTITUT AGAMA ISLAM NEGERI AMBON, 2026)
This study aims to develop and validate a performance assessment instrument for school principals to evaluate their effectiveness in supporting technology-enhanced biology learning and environmental literacy at the secondary school level. The research employed a Research and Development (R&D) approach consisting of four major phases: needs analysis, construct formulation and indicator development, expert validation, and field testing. The instrument was constructed based on nine domains of instructional leadership relevant to 21st-century biology education: learning outcomes, curriculum management, content organization, learning processes, independent learning, technological support, supervised learning visits, adaptability in instructional implementation, and learning evaluation. Expert judgment indicated strong content validity across all domains, with minor revisions suggested for clarity. Field testing conducted in several secondary schools demonstrated that the instrument possesses high internal consistency, indicating reliable measurement. The findings reveal that the instrument is capable of capturing critical dimensions of leadership performance that influence the quality of biology learning, particularly in relation to technology integration and environmental literacy. The developed instrument is recommended for use as an evaluative tool and as a basis for designing professional development programs to enhance school principals’ capacity to lead adaptive, contextual, and sustainability-oriented biology education. Keywords: Principal performance, Instructional leadership, Biology education, Environmental literacy, Educational technology